Worldview and religious-cultural orientations of the "Digital Age Human" - Наргіз Меджідова (Cхід)
This article explores the impact of the digital era on fundamental aspects of human life, including issues of faith, morality, and cultural identity. It highlights that digital technologies have become an integral part of modern human life, making it impossible to ignore their obvious cultural significance today. The focus is on analyzing how contemporary technologies, such as artificial intelligence and the Internet of Things, are reshaping traditional religious practices, facilitating the emergence of new forms of spirituality, and altering traditional religious structures. Both positive and negative consequences of such transformations for individuals and society are discussed. By utilizing digital products and technologies and entering cyberspace, religion strives to make religious heritage, culture, and tradition more understandable and accessible to a larger number of people. The adaptation and transformation of religion can be traced in various directions of activity related to the implementation and mastery of cyberspace and digital space. Examples of the digitalization of religion and religious digital products are provided to substantiate the transformation of religion. The idea is substantiated that studying digital culture today means not so much analyzing its phenomena and artifacts per se, but rather studying the broad transformations occurring with the spread of digital technologies in culture at large.